100 deadly skills survival edition : the SEAL operative's guide to surviving in the wild and being prepared for any disaster - Emerson, Clint (Touchstone, 2016)
"These 100 skills, adapted for civilians from actual field experiences of special forces operations, offer a complete hands-on and practical guide to help you survive in the wild no matter the climate or terrain; be prepared for any crisis; and have the critical life-saving knowledge for staying safe in any hostile environment or disaster."